Modulation of Lipid Transport and Adipose Tissue Deposition by Small Lipophilic Compounds - Castellano, José M.; Espinosa, Juan M.; Perona, Javier S. (Frontiers in Cell and Developmental Biology, 2020)
Small lipophilic molecules present in foods of plant origin have relevant biological activities at rather low concentrations. Evidence suggests that phytosterols, carotenoids, terpenoids and tocopherols can interact with different metabolic pathways, exerting beneficial effects against a number of metabolic diseases. These small molecules can modulate triacylglycerol absorption in the intestine and the biosynthesis of chylomicrons, the lipid carriers in the blood. Once in the bloodstream, they can impact lipoprotein clearance from blood, thereby affecting fatty acid release, incorporation into adipocytes and triglyceride reassembling and deposit. Consequently, some of these molecules can regulate pathophysiological processes associated to obesity and its related conditions, such as insulin resistance, metabolic syndrome and type-2 diabetes. The protective capacity of some lipophilic small molecules on oxidative and chemotoxic stress, can modify the expression of key genes in the adaptive cellular response, such as transcription factors, contributing to prevent the inflammatory status of adipose tissue. These small lipophilic compounds can be incorporated into diet as natural parts of food but they can also be employed to supplement other dietary and pharmacologic products as nutraceuticals, exerting protective effects against the development of metabolic diseases in which inflammation is involved.  The aim of this review is to summarize the current knowledge of the influence of dietary lipophilic small biomolecules (phytosterols, carotenoids, tocopherols and triterpenes) on lipid transport, as well as on the effects they may have on pathophysiological metabolic states, related to obesity, insulin resistance and inflammation, providing an evidence-based summary of their main beneficial effects on human health.